Gualou Guizhi Granule Suppresses LPS-Induced Inflammatory Response of Microglia and Protects against Microglia-Mediated Neurotoxicity in HT-22 via Akt/NF-κB Signaling Pathways. (22nd July 2021) - Chang, Xiaona; Fang, Yaling; Zhang, Yuqin; Liu, Yaojun; Fan, Liming; Nan, Lihong; Xu, Wei; Lin, Yu; Chu, Kedan; Yan, Guohong
Abstract : Neuroinflammation plays a crucial part in the commencement and advancement of ischemic stroke. Gualou Guizhi granule (GLGZG) is known to well exhibit neuroprotective effect, but it is not known whether GLGZG can regulate the inflammatory process at the cellular level in BV2 microglia cells and protect against microglia-mediated neurotoxicity in neurons. Herein, we aimed to investigate the anti-inflammatory effects of GLGZG on BV2 microglia cells and protection against microglia-mediated neurotoxicity in neurons. Methods . The cell model of neuroinflammation was constructed by lipopolysaccharide (LPS) to observe the effect of GLGZG in the presence or absence of GLGZG. The production of nitric oxide (NO), inflammatory mediators, was detected. Moreover, potential mechanisms associated with the anti-inflammatory effect, such as inhibition of microglial activation and nuclear factor kappa B (NF- κ B), were also investigated. In addition, to prove whether GLGZG protects against microglia-mediated neurotoxicity, neuronal HT-22 cells were cultured in the conditioned medium. And cell survivability and neuronal apoptosis of HT-22 were evaluated. Results . It was found that a main regulator of inflammation, NO, is suppressed by GLGZG in BV2 microglial cells. Moreover, GLGZG dose dependently decreased the mRNA and protein levels of inducible NO synthase (iNOS) in LPS-stimulated BV2 cells. Additionally, GLGZG inhibited the expression and secretion of proinflammatory cytokines in BV2 microglial cells. Also, GLGZG inhibited LPS-activated nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) in BV2 microglial cells at the intracellular level. GLGZG significantly affected Akt phosphorylation: phosphorylated forms of Akt increased. To check whether GLGZG protects against microglia-mediated neurotoxicity, neuronal HT-22 cells were incubated in the conditioned medium. GLGZG showed a neuroprotective effect by promoting cell survivability and suppressing neuronal apoptosis. Conclusions . GLGZG exerted its potential effects on suppressing inflammatory responses in LPS-induced BV2 cells by regulating NF- κ B and Akt pathways. In addition, GLGZG could protect against microglia-mediated neurotoxicity in HT-22.